Jetlag prevention in sports - H. M. Zaharodny (National Electronic Information Consortium (NEICON), 2021)
The reasons and mechanisms of development of jetlag in athletes are presented. Organizational solutions of maladaptation prevention are proposed. Proposals for preparation for flight, adjustments for arrival of both medical and pedagogical nature are looked at.